FINANCIAL AND TAX IMPACT IN ECONOMIC MANAGEMENT ACCORDING TO THE DETRACTION SYSTEM - Valencia Gutiérrez, Adolfo (2016)
The State has created prepayment regimes of the “IGV” (GST), to broaden the tax base ensuring collection and avoiding evasion. The mechanisms applied, have only turned the companies into notaries and collectors of SUNAT, it has proceeded to diminish the liquidity of the companies. In particular, the Abatement Scheme is a form of “blind collection” since they do not take into account the actual amount of tax that the taxpayer would be obliged to pay, since the balances in favor or tax credits available to the taxpayer are not considered, who unfairly must distract their financial resources to pay the drawdowns complicating their cash flow and the value of money over time. Also, the study shows the financial and tax impact on the economic management of the application of the Abatement Regime in commercial and industrial companies in Lima Metropolitana, and the results obtained through conducted surveys and the analysis of the results show the negative impact. Most companies face excessive short-term indebtedness, a shortage of liquidity for the payment of their current obligations, which forces them to obtain loans for working capital, generating high financial costs for the payment of interests.